Prinsip Kesamaan Hak Dalam Penguasaan Dan Pemanfaatan Hak Atas Tanah (Studi Kasus Penguasaan Hak Atas Tanah Perkebunan Di Propinsi Jambi) - Sarwani, Raden (Wajah Hukum, 2023)
The principles of equality of control rights and utilization of land rights, to become plantations which are a source of prosperity for all Indonesian people. to obtain a right to land which gives a mandate to the state to maintain a balance with the authority given to the state in the administration, regulation, management and supervision for the purpose of maximizing the prosperity of the people, thereby ensuring the certainty of fair business opportunities for large business actors, medium and small as well as community use of land for plantations by preventing monopolistic practices.This research has a normative legal nature in the form of written positive legal provisions that are applied to legal events in concreto in society, so that in the research there is always a combination of two stages of study. The first stage, the normative approach (library research) is an approach carried out based on primary legal materials or using secondary data including principles, rules, norms and legal rules contained in laws and other regulations. The second stage is the application of in concreto events in order to achieve the predetermined goals. Obtaining data through secondary data in the form of legal and primary materials through interview techniques is carried out directly by conducting structured in-depth interviews.